Acute effects of whole-body vibration on knee joint drop landing kinematics and dynamic postural stability - Delahunt, E.; Crognale, D.; Green, B.; Lonsdale, C.; McGrath, D. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
Whole-body vibration (WBV) is being increasingly utilized in addition to other training modalities in order to prevent and rehabilitate athletic injuries. Excessive knee joint movement has been reported to be a contributing factor to many traumatic and overuse knee joint injuries (Sigward et al., 2008). However the effects of WBV on sensorimotor function and consequent knee joint kinematics is unknown. Thus, the aim of the present study was to examine the effects of an acute WBV exposure on knee joint drop landing kinematics and dynamic postural stability in healthy participants. The null hypothesis was that acute WBV exposure would not influence lower limb drop landing kinematics or dynamic postural stability.